Synergetic approach in trilingua education of the Republic of Kazakhstan - B., Karimova; A., Ongarbayeva; R., Sebepova; A., Aubakirova; M., Mirzabekova (Opción, 2018)
The aim of the article is to present the results of the study of the theoretical foundations and technology of language education in the university as a new paradigm in private didactics. The results of the implementation of the synergistic approach of using the clichéd formulas in the teaching of the Russian language in the conditions of trilingualism: coordination of the lexical-thematic content of the three languages, selfmanagement in the co-study of professional texts, the formality of linguistic, speech, communicative, professional, discursive competence.